Modeling the Influence of Attractive Petroleum Fiscal Regime Dimensions on Marginal Fields' Investment Climate in Malaysia - Masud, Abdulsalam; Manaf, Nor Aziah Abdul; Saad, Natrah (International Journal of Energy Economics and Policy, 2019)
Attractiveness of a country petroleum fiscal system plays significant role in investment location decisions. This study modeled the influence of attractive petroleum fiscal regime dimensions on marginal oil fields' (MOFs) investment climate in Malaysia. The dimensions examined in this study are fiscal administration/economy, fiscal certainty, fiscal efficiency, and fiscal equity/neutrality. Data was collected through survey of accounting, business and taxation experts' within Malaysian MOFs subsector. It was analyzed using Partial Lease Square (PLS) – Structural Equation Modeling (SEM) version 3 and Special Package for Social Science (SPSS) version 19. The results showed that fiscal certainty, fiscal efficiency and fiscal equity/neutrality were found to have significant positive influence on marginal oil fields' investment climate, adversely insignificant influence of fiscal administration/economy on marginal oil fields investment climate was reported. The result has established weaker link between petroleum fiscal regime administration and MOFs' investment climate in Malaysia, thus highlighting the scope for improvement on this dimension. Therefore, it is recommended that concerned authorities should consider strengthening of the administrative framework of MOFs' fiscal regime, thereby enhancing its investment climate. To the best of our knowledge this is the first study that employed the use of experts' perception in modeling the influence of attractive fiscal regime dimensions on oil and gas fields' investment climate, and eventually investment location decisions. Keywords: attractive petroleum fiscal regime, investment climate, investment location decision JEL Classifications: M4, M48, Q4, Q48 DOI: https://doi.org/10.32479/ijeep.7721